Immunohistochemical expression of the proliferative marker Ki67 in hydatidiform moles and its diagnostic value in the progression to gestational trophoblastic neoplasia. Issue 2 (26th August 2012) - Hasanzadeh, Malihe; Sharifi, Nourieh; Esmaieli, Habibollah; Daloee, Mahdi Sharife; Tabari, Azadeh
Abstract Aim: Considering that Ki‐67 is a proliferative marker in molar pregnancies and the possible progression of these kinds of pregnancies to gestational trophoblastic neoplasia (GTN), we decided to evaluate the rate of expression of this marker in patients with uneventful hydatidiform moles and GTN. Moreover, we determined the predictive value of this factor for the progression of molar pregnancies to GTN. Methods: In two groups of patients, including 30 patients with uneventful molar pregnancies and 30 patients with GTN, an immunohistochemical staining technique using the Envision method was performed. To evaluate nuclear immunoreactivity of trophoblastic cells for Ki67 on paraffin sections obtained from molar pregnancy products, the percentage of the stained cells was used. Semi‐quantitative evaluation was also performed. Data were analyzed using Mann–Whitney tests and receiver operating characteristic curve analysis. Results: The expression of Ki67 in cytotrophoblastic and syncytiotrophoblastic cells of patients with GTN was significantly more than for patients with an uneventful molar pregnancy (P < 0.05). We considered a 12.5% cut‐off value for Ki67 in cytotrophoblastic cells and a sensitivity of 90%, specificity 93%, positive predictive value of 93.1% and negative predictive value of 90.3% were obtained. Similarly, considering a cut‐off value of 6% for Ki67 in syncytiotrophoblastic cells, results of 90% were obtained for all diagnostic indices. Conclusion: Our findings suggest that expression of the Ki67 oncogene in trophoblastic cells in patients with GTN are found far more frequently than in patients with an uneventful molar pregnancy, and demonstrate a high predictive value of progression to GTN.